CD8+ T Cell Hyperfunction In Advanced Liver Fibrosis Murine Model and Its Association with Tumor Growth - Madani, Jood (Université d'Ottawa / University of Ottawa, 2022)
Advanced liver fibrosis in chronic hepatitis C infection (HCV) is associated with a generalized impaired immune system. Many immune cells are affected in chronic liver disease, including CD8+ T cells. The Crawley lab reported CD8+ T cell hyperfunction in cirrhotic HCV-infected individuals that persisted after effective antiviral therapy. To evaluate the link between CD8+ T cell dysfunction in advanced fibrosis, we adapted a hepatotoxic carbon tetrachloride (CCl4) murine model. We consistently observed severe fibrosis in CCl4-treated mice resembling fibrosis in chronic HCV infected individuals. After stimulation of PBMC, the proportion of granzyme B+, and IFN-γ+ CD8+ T cells in fibrotic mice was significantly higher than the controls, particularly naïve and central memory CD8+ T cells. This state of hyperfunction was sustained after liver insult removal and significant fibrosis regression to near normal tissue integrity. Sex differences were also studied in this model and were apparent after prolonged exposure to CCl4 and in the capacity to repair liver fibrosis. Following an ectopic challenge with cancer cells, tumor growth was significantly greater in fibrotic mice. Moreover, the response to immunotherapy was significantly delayed in CCl4-treated mice. In summary, we reported for the first time that circulating CD8+ T cells are hyperfunctional in a murine model of advanced liver fibrosis in response to a hepatotoxin. In this context, affected mice failed to control the growth of a tumor whose growth is known to be controlled by a robust CD8+ T cell response. In addition, the reduced responses to immunotherapeutic effects suggest deficiencies in antigen-specific CD8+ T cell responses. Therefore, this animal model might be useful to identify mechanistic targets with translational potential for immune restoring treatments in human chronic liver diseases with advanced liver fibrosis.
Keywords: Advanced liver fibrosis; CD8 T cells; Mouse model; Immune cells; HCV infection